COVID-19 and sustainable development in Somalia/Somaliland - Eric Herring; Peter Campbell; Mustafe Elmi; Latif Ismail; Jamal Jama; Sandra McNeill; Abdi Rubac; Asma Saed Ali; Amel Saeed; Muna Yusuf (Taylor & Francis Group, 2020)
The research aimed to understand the impact of COVID-19 and responses to it on sustainable development in Somalia and its breakaway region Somaliland. It explored how sustainable development could be protected and promoted through, during and as a method of COVID-19 response. It explored the themes of lives, livelihoods and inclusion. Due to COVID-19, it used three non-face-to-face methods: desk-based analysis of literature and secondary data; 175 phone interviews; and five phone Focus Group Discussions. The research was co-produced with 40 participants, which ensured that the study was carried out with as well as for those who could potentially benefit from it. COVID-19 and responses to it have generated intense and multi-dimensional concerns and deprivation, especially among those on low incomes. Livelihoods are being destroyed but people are receiving little or no financial support. People are receiving too little help to cope with the many problems they face. Limited action to prevent COVID-19 infection is more due to structural and social factors than lack of information. Public health education is still necessary; it should include challenging stigmatisation, explaining that wearing a face covering does not mean a person is infectious, and explaining that those recovered from the virus are not still infectious. Health care is mostly unavailable, unaffordable and not trusted. There is broad and deep agreement across all major issues explored in the research, including the immediate actions needed and the fundamentals of what building back better would mean. Responses to COVID-19 have mainly had the effect of undermining the prospects for sustainable development in Somalia/Somaliland. Despite this, the existence of broad and deep agreement on the major issues explored in the research could form the basis of a new commitment to sustainable development.